KINERJA DAN AKUNTABILITAS LEMBAGA AMIL ZAKAT DI KABUPATEN JEMBER - Chotib, Moch (Universitas Muhammadiyah Jember, 2017)
ABSTRACTZakat is part of the pillars of Islam. So as a consequence, Muslims are obliged to pay zakat as a duty of their religion. On the other hand, zakat has a humanitarian function (read: social concern for others). According to Qardlawi (1970), one fundamental and fundamental effort to eradicate or minimize the problem of poverty is by optimizing the implementation of zakat. That's because zakat is a source of funds that will never dry and run out. In other words as long as Muslims have an awareness of zakat and as long as the zakat funds are well managed, the zakat funds will always be there and beneficial to the interests and welfare of society, therefore to see the importance of seeing the performance and accountability of the Institute of Amil Zakat (LAZ) in Jember District. The purpose of this study is to analyze and collaborate and describe the fund management process at each LAZ in Jember District. Qualitative studies of the science of administration often use qualitative study methods with case study approaches. The use of qualitative review method with case study approach in this study is important, in order to be able to capture phenomena related to performance and accountability of Lembaga Amil Zakat (LAZ) in Jember District. Based on the results of the study can be concluded that: 1). Aspects of Innovation in the management of LAZ, LAZ National is more innovative than the Local LAZ. 2). Aspects of local wisdom (local wisdom), local LAZ is more innovative, because the National LAZ only does what is central LAZ (read: Parent). 3). Reporting Aspect, National LAZ is more tiered in its reporting from regional to central level both to the central agency (LAZ Center) and to government agencies or government-appointed agencies based on legislation. Whereas the local LAZ only reports to local government agencies or government-appointed agencies based on laws and regulations, and 4). Financial reporting aspect, National LAZ is more obedient by following rules of law by making standard accounting report of zalcat by making Statement of Financial Accounting Standard 109 (PSAK 109), while LAZ Local has not made standard financial report PSAK 109.Keywords: Lembaga Amil Zakat, Performance and Accountability